Cooperative Syngas Production and C−N Bond Formation in One Photoredox Cycle. Issue 14 (24th February 2021) - Han, Chuang; Li, Yue‐Hua; Li, Jing‐Yu; Qi, Ming‐Yu; Tang, Zi‐Rong; Xu, Yi‐Jun
Abstract: Solar‐driven syngas production by CO2 reduction provides a sustainable strategy to produce renewable feedstocks. However, this promising reaction often suffers from tough CO2 activation, sluggish oxidative half‐reaction kinetics and undesired by‐products. Herein, we report a function‐oriented strategy of deliberately constructing black phosphorus quantum dots‐ZnIn2 S4 (BP/ZIS) heterostructures for solar‐driven CO2 reduction to syngas, paired with selectively oxidative C−N bond formation, in one redox cycle. The optimal BP/ZIS heterostructure features the enhanced charge‐carrier separation and enriched active sites for cooperatively photocatalytic syngas production with a tunable ratio of CO/H2 and efficient oxidation of amines to imines with high conversion and selectivity. This prominent catalytic performance arises from the efficient electronic coupling between black phosphorus quantum dots and ZnIn2 S4, as well as the optimized adsorption strength for key reaction intermediates, as supported by both experimental and theoretical investigations. We also demonstrate a synergistic interplay between CO2 reduction and amine dehydrogenation oxidation, rather than simply collecting these two single half‐reactions in this dual‐functional photoredox system. Abstract : A function‐oriented strategy of engineering black phosphorus quantum dots‐ZnIn2 S4 heterostructures for solar‐driven CO2 reduction to syngas, paired with selectively oxidative C−N bond formation, in one redox cycle is reported. The promoted charge‐carrier separation, enriched active sites and optimized adsorption strength of key reaction intermediates for CO2 reduction, as well as the cooperative photoredox manner, jointly contribute to the enhanced photoactivity and selectivity.